Vtisni zlom golenične grče - tipična poškodba zareznega smučanja - Veselko, Matjaž (Zdravniški vestnik, 2008)
Background Depression fractures of the tibial condyles due to sudden turn of one ski are more frequent ski injury than it used to be. There seems to be a correlation between this injury and carving skies. Methods All depression fractures of the tibial condyles due to skiing injuries during 2004 and 2005, have been analysed with regard to mechanism of injury and fracture type. To explain the mechanism of injury due to sudden turn of ski with carved edges, mathematical model was used. Results 48 patients were treated for fracture of the proximal tibia. 18 of these were depression fractures of a tibial condyle,13 lateral and 5 medial. All skiers skied on skies with carved edges. Mechanism of injury was in all cases of fracture of the medial condyle sudden turn of the ski inwards and in lateral condyle, outwards. Mathematical model of the influence of carving on the knee injury type has shown that force transmitted to lower limb is dependant on velocity and on the radius of the curvature at ski turn, and this is determined by the radius of the curvature of the edge of the ski. This force can be multiplied by additional decrease ofthe radius due to instant additional bowing of skies, for instance when running into a sharp depression. Conclusions In this paper we present typical mechanism of the fracture of the tibial condyle, due to sudden turn of the skiwith carved edges. Mathematical model explains how the force transmitted tothe knee multiplies due to sudden decrease of the carved turn radius, or dueto
Keywords: Biomechanics; Biomehanika; Knee Injuries; Koleno, poškodbe; poškodbe; Skiing; Smučanje; Tibia, zlomi; Tibial Fractures; zlomi